1996
DOI: 10.1080/135765096397793
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Processing Asymmetries Between the Cerebral Hemispheres: Evidence and Implications

Abstract: This paper reviews a large body of research which has investigated the capacities of the cerebral hemispheres to process temporal information. This research includes clinical, non-clinical, and electrophysiological experimentation. On the whole, the research supports the notion of a left hemisphere advantage for temporal resolution. The existence of such an asymmetry demonstrates that cerebral lateralisation is not limited to the higher-order functions such as language. The capacity for the resolution of fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 92 publications
(151 reference statements)
4
26
0
Order By: Relevance
“…In terms of cerebral lateralisation, Peretz and Morais [43] suggested that metric organisation may be ascribed to the right hemisphere, whilst smaller rhythmic groupings are encoded by the left hemisphere. This notion is consistent with research findings from normal subjects [12,18,52] and brain-damaged patients [11,30,44], as well as data supporting left hemispheric specialisation of temporal processing relevant to speech perception [33,34,51,54]. Neuropsychological studies of groups of patients, however, have generally shown more variable lateralisation effects, particularly in recent research [25,36,46].…”
Section: Introductionsupporting
confidence: 89%
“…In terms of cerebral lateralisation, Peretz and Morais [43] suggested that metric organisation may be ascribed to the right hemisphere, whilst smaller rhythmic groupings are encoded by the left hemisphere. This notion is consistent with research findings from normal subjects [12,18,52] and brain-damaged patients [11,30,44], as well as data supporting left hemispheric specialisation of temporal processing relevant to speech perception [33,34,51,54]. Neuropsychological studies of groups of patients, however, have generally shown more variable lateralisation effects, particularly in recent research [25,36,46].…”
Section: Introductionsupporting
confidence: 89%
“…Behavioral and fMRI evidence also closely ties the basal ganglia to the processing of temporal discrimination thresholds (the perception of rapidly presented stimuli as either simultaneous or sequential) (Fiorio et al, 2003); to motor timing (Grasso et al, 1999;Harrington et al, 1998;Malapani et al, 2002) and to duration estimation (Ferrandez et al, 2003;Harrington et al, 1998; 14 Nenadic et al, 2003). Moreover, just as the left hemisphere is particularly important for procedural memory, so it also appears to be crucial for rapid temporal processing: Evidence suggests that the left hemisphere has better temporal resolution than the right, and may be specialized for much shorter periods of temporal integration (Allard and Scott, 1975;Hickok and Poeppel, 2000;Ivry and Robertson, 1998;Nicholls, 1996;Zatorre et al, 2002). Intriguingly, the timing and rapid processing functions of the brain structures underlying the procedural system appear to be linked to other functions of this system.…”
Section: Temporal Processingmentioning
confidence: 99%
“…Indirect evidence for this e ect comes from Tramo and Gazzaniga [35], whose study of split-brain patients found a left hemisphere advantage for the identi®cation of common musical instruments. Secondly, the investigations failed to distinguish between the stationary and temporal aspects of timbre perception and it could be argued that reliance on temporal vs stationary cues may diminish or even reverse the laterality e ects, since it is generally accepted that the left hemisphere is better at discriminating ®ne temporal events (see [19] for a review).…”
Section: Introductionmentioning
confidence: 99%